MiR-497-5p Regulates Osteo/Odontogenic Differentiation of Stem Cells From Apical Papilla via the Smad Signaling Pathway by Targeting Smurf2 - Liu, Junqing; Wang, Xiaolong; Song, Mengxiao; Du, Jing; Yu, Jiali; Zheng, Wenzhou; Zhang, Chengfei; Wang, Yan (Frontiers in Genetics, 2020)
Osteo/odontogenic differentiation is a key process of human stem cells from apical papilla (SCAP) in tooth root development. Emerging evidence indicates microRNAs (miRNAs) play diverse roles in osteogenesis. However, their functions in osteo/odontogenic differentiation of SCAP require further elucidation. To investigate the role of miRNA in SCAP osteo/odontogenic differentiation and underlying mechanisms, miRNA microarray analysis was performed to screen differentially expressed miRNAs between control and osteo/odontogenic-induced group. Quantitative real-time PCR (qRT-PCR) and western blot were used to detected osteo/odontogenic differentiation-related markers and possible signaling pathway SCAP-associated genes. Alizarin Red Staining (ARS) were applied to evaluated osteogenic capacity. The results showed that miR-497-5p increased during SCAP osteo/odontogenic differentiation. Overexpression of miR-497-5p enhanced the osteo/odontogenic differentiation of SCAP, whereas downregulation of miR-497-5p elicited the opposite effect, thus suggesting that miR-497-5p is a positive regulator of the osteo/odontogenic differentiation of SCAP. Bioinformatic analysis and dual luciferase reporter assay identified that SMAD specific E3 ubiquitin protein ligase 2 (Smurf2) is a direct target of miR-497-5p. Further study demonstrated that Smurf2 negatively regulates SCAP osteo/odontogenic differentiation, and silencing Smurf2 could block the inhibitory effect of the miR-497-5p inhibitor. Meanwhile, pathway detection manifested that miR-497-5p promotes osteo/odontogenic differentiation via Smad signaling pathway. Collectively, our findings demostrate that miR-497-5p promotes osteo/odontogenic differentiation of SCAP via Smad signaling pathway by targeting Smurf2.